SOME PSYCHOLOGICAL CONSEQUENCES OF THE COVID-19 PANDEMIC AND THE WAR OF 2020 IN ARMENIA - Tatevian, H.A. (Modern Psychology, 2021)
The given study focuses on the psychological impact of COVID 19 and the latest Karabakh war in 2020 on the people of Armenia. In particular, some results of a study of the psychological consequences of combined psychological trauma on young people of both sexes are presented. The data obtained with regard to anxiety levels and extraversion are of particular interest. The study population included those who had been exposed or not to the coronavirus, as well as young people who had participated and those who hadn’t participated in the war. The results obtained also reflect, to a certain extent, the peculiarities of the general psychological state of the country's population.
Keywords: COVID 19; War; Anxiety; Psychological Trauma; PTSD.